OPTIMIZING THE ROLE OF NURSING AND HEALTH PROFESSIONALS TO ENHANCE HEALTH CARE QUALITY IN THE NEW NORMAL ERA - Indah Jayani; Susmiati Susmiati (UNEJ e-Proceeding, 2020)
The phenomenon of the COVID-19 pandemic has become a global issue since the end of 2019. Almost all parts of the world are affected by (SARS-CoV-2). Indonesia has reported 207,203 positive cases, the second-most in Southeast Asia after the Philippines. Indonesia is the third-largest in Asia, with 8,456 deaths (Worldometer, 2020). Obtained Various information about the risk factors for COVID-19, which stated that people with HIV / AIDS have a higher risk. The threat of decreasing the quality of life, both physically, psychologically, and socially, creates an impact of worry and anxiety, aggravating the disease. This study aims to determine the quality of life of PLWHA and the relationship between demographic factors and the quality of life of PLWHA. The design of this research is quantitative descriptive-analytic using a crossectional approach. Analyze data to link demographic characteristics such as; gender, age, education, occupation, marital status, and living with family used the Spearman Rank correlation with a significance value of α = 0.05. The sample size in this study amounted to 37 people who were selected by purposive sampling technique. The research instrument used was the WHOQOL-HIV BREF. The results showed that almost all of the quality of life of PLHIV was in the wrong category at 78.4%. There was a relationship between gender, age, and education factors with the quality of life of PLWHA with p-value <α = 0.05. And there is no relationship between work factors, marital status, and living with family indicated by p value> α = 0.05. It hopes that supports from all sectors of society and the government provide support for PLWHA so that the quality of life for PLWHA increases to survive during the COVID-19 pandemic. Keywords: Quality of Life, PLWHA, COVID-19